PDA Activities for Palms Using Microsoft Outlook - Barksdale, Karl (Cengage Learning, Inc, 2007)
The PDA is an emerging input technology that is becoming standard in both the office and the classroom. It is becoming essential to teach students the proper use of PDAs. PDA ACTIVITIES FOR PALMS is designed as a short unit of instruction that is easy to incorporate in existing courses or combine with other units such as speech recognition, Web page design, or application software